Environmental Risk Factors for Endometriosis: An Umbrella Review of a Meta-Analysis of 354 Observational Studies With Over 5 Million Populations - Zhang, Ye; Ma, Ning-Ye (Frontiers in Medicine, 2021)
Background: The association of a diverse array of environmental risk factors with risk of endometriosis is contradictory. Objective: To summarize the evidence of associations between environmental risk factors and endometriosis risk. Methods: PubMed, EMBASE, Web of Science and ClinicalTrial.gov databases were systematically searched in June 2020. Meta-analyses of Observational studies investigated any environmental exposure (non-genetic) and endometriosis risk. For each article, we estimated the summary effect size, 95% confidence intervals (CIs), and the 95% prediction interval. We also estimated the between-study heterogeneity expressed by I2, evidence for small-study effects, and evidence of excess significance bias. Results: Twelve eligible articles (featuring 143422 cases and 5112967 participants) yielded data on 40 unique environmental risk factors, including life styles (n=16), reproductive factors (n=3), early life factors (n=4), and a range of other risk factors (e.g., phthalate metabolites, endocrine-disrupting chemicals, and body mass index). Twenty-five of these 40 associations (62.5%) were statistically significant (P<0.05) under random-effects models. Evidence for an association was indicated for alcohol intake (relative risk [RR]: 1.25; 95%CI: 1.11-1.41) and exposure to EDCs (RR: 1.41; 95%CI: 1.23-1.60), while 15 associations presented only weak evidence. Conclusions: Our analyses showed that alcohol intake and exposure to endocrine-disrupting chemicals may be potential risk factors for endometriosis and supported by suggestive epidemiological evidence. However, it was evident that there was substantial heterogeneity and/or bias between the different studies featured in the various meta-analyses included in this review; therefore, the outcomes of our analysis should be interpreted cautiously.